Spectrum and network measurements - Witte, Robert A. (Scitech Publishing, an imprint of IET, 2014)
The book has 17 chapters and these chapters are dealt with: spectrum measurement; Decibels; Fourier theory; fast Fourier transform analyzer; swept spectrum analyzer; modulation measurement; distortion measurement; noise measurement; pulse measurement; filtering; averaging; transmission lines; two-port network; network analyzer; vector network measurement; and EMC measurement.
Keywords: Spectrum analyzers.; Electric network analyzers.; elektronické knihy; electronic books